2002
DOI: 10.1097/00003246-200206000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Inspired superoxide anions attenuate blood lactate concentrations in postoperative patients

Abstract: Inspired O(2)(-) attenuates blood lactate concentrations. This may be attributed, in part, to the systemic stimulatory effect on superoxide dismutase activity, which accelerates oxidative phosphorylation in the mitochondria, thus attenuating lactate generation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…It has been demonstrated that the former air ions reach the alveoli of the lungs (Duan et al., 1994). Water binding may cause a marked difference in the half time of these ions, which is about 60 s for the ions produced by water shearing and several seconds for those produced by corona discharge (Iwama et al., 2002). The present results show that only the negative air ions created by water shearing have a biologic action, decreasing blood lactate levels, increasing blood pH and improving erythrocyte deformability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been demonstrated that the former air ions reach the alveoli of the lungs (Duan et al., 1994). Water binding may cause a marked difference in the half time of these ions, which is about 60 s for the ions produced by water shearing and several seconds for those produced by corona discharge (Iwama et al., 2002). The present results show that only the negative air ions created by water shearing have a biologic action, decreasing blood lactate levels, increasing blood pH and improving erythrocyte deformability.…”
Section: Discussionmentioning
confidence: 99%
“…The latter method only generates superoxide ions (O) attached to microclusters of water showing a structure of O(H 2 O) n (Kosenko et al., 1997), and is essentially considered a natural source of negative air ions. Negative air ions in the form of O(H 2 O) n have a half‐life of about 60 s, and are markedly different from those created by corona discharge, which disappear within several seconds, probably because of the absence of water binding (Iwama et al., 2002). High levels of negative air ions created by water shearing are observed near waterfalls, ranging from 2000 to 10,000 ions/cm 3 in my experience.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When NAIs combined with water molecules and form negative-ion clusters, their lifetime will be longer. For example, the half-life of negative oxygen ions O 2 − (H 2 O) n by the Lenard effect is around 60 seconds, but the NAIs generated by corona discharge could survive only several seconds [ 32 ]. Such a trend in survival duration of these two different sources of NAIs was also observed by another study [ 33 ].…”
Section: Negative Air Ions and Their Generationmentioning
confidence: 99%
“…There are many references to report the possible biological effects [ 24 , 32 , 33 , 35 , 38 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 ]. And some of them were listed in Table S2 .…”
Section: Biological Effects Of Negative Air Ions On Human/animal Hmentioning
confidence: 99%